Pengaruh Budaya Organisasi Yang Positif Terhadap Retensi Karyawan di UMKM Bakpia Lanank Jogja - Dian Lestari; Kristiana Sri Utami (Universitas 45 Surabaya, 2024)
This study aims to explore the positive organizational culture and factors influencing employee retention at Bakpia Lanank Jogja. The research methodology employed a qualitative approach, gathering data through observations and interviews with company employees. The findings indicate that the majority of employees perceive a positive organizational culture, particularly in terms of job security, cooperation, company support, openness, and job appreciation. Additionally, factors such as well-designed job roles, clear career opportunities, and a positive work environment also contribute to employee retention in this company. These results provide valuable insights for company management to maintain and enhance a positive organizational culture and employee retention strategies in the future.